Dependency on Artificial Intelligence, Study Habits, and Geometry Achievement of College Students at Davao del Norte State College - Queenzel Nicole E. Taboco; Ryza Mae Mangalaw; Stephen E. Salvacion; Regie M. Angkahas; Abel E. Sadji (Journal of Social, Humanity, and Education, 2026)
Purpose: This study aimed to determine whether artificial intelligence dependency and study habits can predict students’ achievements in geometry. Research Methodology: A quantitative descriptive-correlational design was employed to describe the general findings of the study, using three adapted and validated questionnaires to measure and determine the predictive influence of dependency on artificial intelligence and study habits on students’ geometry achievement among 120 first and second year Bachelor of Secondary Education (BSEd) Mathematics students from Davao del Norte State College, selected through simple random sampling. Results: Based on the results, respondents frequently used artificial intelligence tools and demonstrated generally positive study habits, and their overall performance in geometry was very satisfactory. However, statistical analysis using the mean, standard deviation, and Pearson’s r showed no significant relationship between dependency on artificial intelligence and geometry achievement or between study habits and geometry achievement, indicating that these variables did not influence students’ performance in the subject. Conclusions: There is no significant relationship between dependency on artificial intelligence and geometry achievement, as well as between study habits and geometry achievement Limitations: The findings suggest that dependency on artificial intelligence and study habits are not strong predictors of success in geometry. Contributions: This study recommends exploring other factors, such as motivation, teaching strategies, and technological literacy, that may better explain variations in academic performance and guide educators in designing more effective interventions to improve students’ learning outcomes in geometry.